Acceleration of microwave-assisted extraction processes of food components by integrating technologies and applying emerging solvents: A review of latest developments. (September 2017) - Ekezie, Flora-Glad Chizoba; Sun, Da-Wen; Cheng, Jun-Hu
Abstract: Background: Microwave-assisted extraction (MAE) have gained enormous popularity as a preferred method for the recovery of various active compounds from food materials. They proffer benefits such as the reduction of extraction time, environmental friendliness, low cost and enable automation or on-line coupling to other analytical procedures. Recently, newer add-ons or technological modifications have been incorporated into MAE systems, in an effort to continuously improve extraction efficiency and ensure a greener implementation. Scope and approach: The core pathways of such meliorations include integrating microwave extraction with other technologies, e.g., ultrasound assisted extraction (UAE), negative pressure cavitation (NPC), enzyme assisted extraction (EAE), hydrodiffusion extraction (HDE), and supercritical fluid extraction (SFE) or replacement of extraction medium with suitable alternatives including ionic liquids, deep eutectic solvents, non-ionic surfactants, etc. This review confers their underlying principles and mechanisms, equipment and apparatuses, practicalities, as well as resultant benefits such as increased yield, intensification of mass transfer and reduction of energy consumption, in a manner not achievable by MAE alone or previous intermediary modifications. Key findings and conclusions: It is hoped that this paper reinforces the need to initiate more studies focused on process validation and optimization of such emerging MAE systems, in furtherance of their scale-up, sustainability and robust adoption by the food industry. Highlights: Recent developments in microwave-assisted extraction techniques were discussed. Basic principles governing these emerging extraction procedures were highlighted. Combination with other technologies maximizes yields of target food components. Integrating alternative and greener solvents promotes overall extraction efficiency. Future research trajectories to facilitate their adoption were proposed.